2010
DOI: 10.1039/b924149c
|View full text |Cite
|
Sign up to set email alerts
|

Development of anomalous diffusion among crowding proteins

Abstract: In cell membranes, proteins and lipids diffuse in a highly crowded and heterogeneous landscape, where aggregates and dense domains of proteins or lipids obstruct the path of diffusing molecules. In general, hindered motion gives rise to anomalous transport, though the nature of the onset of this behavior is still under debate and difficult to investigate experimentally. Here, we present a systematic study where proteins bound to supported lipid membranes diffuse freely in two dimensions, but are increasingly h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 58 publications
(98 reference statements)
7
97
0
Order By: Relevance
“…Molecular motion in these crowded membranes may therefore be restricted by the high protein content. Consistent with this theory, it has been demonstrated that D L decreases linearly with respect to increasing 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 (Ramadurai et al, 2009) and SLBs (Horton et al, 2010). Membrane-embedded proteins that interact with the cytoskeleton naturally display restricted lateral diffusion (Valentine and Haggie, 2011;Haggie et al, 2006).…”
Section: Measurements Of D L In Biogenic Membranessupporting
confidence: 56%
“…Molecular motion in these crowded membranes may therefore be restricted by the high protein content. Consistent with this theory, it has been demonstrated that D L decreases linearly with respect to increasing 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 (Ramadurai et al, 2009) and SLBs (Horton et al, 2010). Membrane-embedded proteins that interact with the cytoskeleton naturally display restricted lateral diffusion (Valentine and Haggie, 2011;Haggie et al, 2006).…”
Section: Measurements Of D L In Biogenic Membranessupporting
confidence: 56%
“…To further explore the discrepancy in anomalous exponent uncovered between individual ACFs and the diffusion law, we used an ACF inversion method originally proposed by Shusterman et al 39,40 , and later put forward in the context of anomalous diffusion studies 29,41,45 . This method allows extracting a function directly from the ACF, MSD ACF (τ), which corresponds to the mean-squared displacement of the particles as long as their diffusion is governed by a Gaussian propagator (see section 2.1).…”
Section: Resultsmentioning
confidence: 99%
“…A second type of analysis was performed on the ACF obtained for the protein samples to test the nature of the diffusion, as suggested recently 29,41,45 . After normalization of the experimental ACFs in order to bring the amplitude of the diffusive part to 1, Eq.…”
Section: Analysis Of Autocorrelation Functionsmentioning
confidence: 99%
“…Thus, it can be treated as a representative, interesting and challenging problem. 15,16 Experimental studies concerning the motion of proteins and lipids in cells were performed using uorescence correlation spectroscopy, [17][18][19][20] pulsed eld gradient NMR 21 and single particle tracking (SPT). 6,7,[22][23][24][25][26][27] In many cases an anomalous diffusion was detected, i.e.…”
Section: Introductionmentioning
confidence: 99%